Effects of the German skin cancer screening programme on melanoma incidence and indicators of disease severity3. (6th September 2016) - Trautmann, F.; Meier, F.; Seidler, A.; Schmitt, J.
Summary: Background: In Germany a nationwide melanoma screening programme for adults aged ≥ 35 years was introduced in July 2008. Evidence on utilization and effects is limited. Objectives: To examine the uptake and effects of the German nationwide screening programme. Methods: This analysis is based on pseudonymized outpatient routine data of a German health insurance company covering data of > 2 million individuals from Saxony for the years 2005–2012. Cases of melanoma and nonmelanoma skin cancer (NMSC) were identified using an algorithm based on the International Classification of Diseases, 10th Revision. Cross‐sectional and longitudinal analyses were applied to determine the utilization of the screening programme and effects on skin cancer incidence and disease severity as a proxy for prognosis. Results: Overall, 38·0% of eligible persons (≥ 35 years) were screened at least once between July 2008 and December 2012. The annual participation rate was 12·4%. Out of 533 393 persons screened, melanoma and NMSC were diagnosed in 0·3% and 2·5%, respectively. The 6‐month melanoma incidence per 100 000 insured persons decreased from 12·8 before screening introduction (January to June 2008) to 10·2 after introduction (July to December 2008). NMSC incidence increased from 173·8 to 175·5 per 100 000. The numbers of screening participants receiving interferon alpha and/or being diagnosed with lymph node and/or distant metastasis (8·6%, 5·9%, 1·5%, respectively) were lower than in nonparticipants (11·2%, 8·5%, 3·5%). These differences were not significant. Conclusions: The results suggest that the introduction of a generic skin cancer screening programme in Germany was not associated with significant changes in incidence. No firm conclusions regarding the effects of skin cancer screening on prognosis can be drawn. Longer follow‐up and linkage with clinical registry data are necessary to clarify the effect of screening participation on incidence and prognosis. Abstract : What's already known about this topic? Evidence on the utilization and effects of the German nationwide screening programme for melanoma introduced in 2008 is limited. What does this study add? The annual participation rate was 12·4% among all eligible persons (age ≥ 35 years). No significant increase in melanoma incidence was found after introduction of the screening programme. Fewer patients with melanoma within the screening programme were diagnosed with metastasis and/or received interferon alpha treatment compared with patients never participating in the programme. Linked Comment: Eisemann. Br J Dermatol 2016;175 :862 . Plain language summary available online